REFORMASI PARTAI POLITIK DALAM RANGKA PENGUATAN FUNGSI REKRUTMEN POLITIK PARTAI POLITIK - NIM. A1011191134, GILANG RAMADHAN (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract In a democracy, the role of political parties is very important, there is even an assumption that there is no democracy without political parties. In Indonesia alone, the state constitution even mentions political parties six times. One of the functions that makes the role of political parties so important for democracy is political recruitment and as a means of filling political positions in the executive and legislative branches. However, according to the Political Indicators survey, political parties and the House of Representatives are the two democratic institutions that are least trusted by the public with a score of 58.7% for political parties and 61.4% for the House of Representatives. One of the factors influencing this is the quality of the results of political recruitment that has not been maximized by political parties. The output of political party recruitment and regeneration that has not been maximized is also influenced by the input processes of political party recruitment and regeneration that are still not optimal. Political parties are still not well institutionalized as democratic institutions to carry out the political recruitment function. Political party reform is needed to maximize the function of political recruitment.This research is a normative legal research using a conceptual approach. This research aims to provide methods of political party reform.The result of this research is that there are six indicators that need to be reformed to strengthen political parties; ideology, regeneration system, funding, public image, women's representation, and internal political party conflicts. And the steps that can be taken are reforming political parties towards the typology of progamic political parties as an effort to revive the political recruitment function of political parties; Reviving the function of democratic political recruitment to recruit political officials trusted by the community; Implementing a limited open list proportional election system.Keywords: Political Party; Political Recruietment; Political Party Reform. Abstrak Di dalam demokrasi peranan partai politik sangatlah penting, bahkan ada anggapan tiada demokrasi tanpa partai politik. Di Indonesia sendiri bahkan konstitusi negara menyebutkan partai politik sebanyak lima kali. Salah satu fungsi yang membuat peranan partai politik begitu penting bagi demokrasi adalah rekrutmen politik dan sebagai sarana pengisian jabatan politik di eksekutif dan legislatif. Namun menurut survei Indikator Politik menempatkan partai politik dan lembaga legislatif DPR RI sebagai dua institusi demokrasi yang paling tidak dipercayai masyarakat dengan nilai 58,7% untuk partai politik dan 61,4% untuk DPR. Salah satu faktor yang memengaruhi hal tersebut adalah kualitas daripada hasil rekrutmen politik yang belum maksimal dari partai politik. Output dari rekrutmen dan kaderisasi partai politik yang belum maksimal dipengaruhi juga oleh proses-proses input rekrutmen dan kaderisasi partai politik yang masih belum maksimal. Partai politik masih belum terlembaga dengan baik sebagai iJingga Ramadhantiya, Yang Hilang Dari Reifikasi Partai Di Indonesia, Medium. https://medium.com/@dhintya22/yang-hilang-dari-reifikasi-partai-di-indonesia-467f88aa47a4 Diakses pada 11 Desember 2023 pukul 07.09 WIB.nstitusi demokrasi untuk menjalankan fungsi rekrutmen politik tersebut. Diperlukannya reformasi partai politik untuk memaksimalkan fungsi rekrutmen politik.Penelitian ini merupakan penelitian hukum yang bersifat normatif dengan menggunakan pendekatan konsep. Penelitian ini bertujuan untuk memberikan metode-metode reformasi partai politik sebagai langkah memperkuat fungsi rekrutmen politik partai politik. Hasil dari penelitian ini adalah terdapat enam indikator yang perlu direformasi partai politik untuk memperkuat partai politik; ideologi, sistem kaderisasi, pendanaan, citra publik, keterwakilan perempuan, dan konflik internal partai politik. Dan langkah yang dapat diambil adalah mereformasi partai politik kearah tipologi partai politik progamatik sebagai upaya penghidupan fungsi rekrutmen politik partai politik; Penghidupan kembali fungsi rekrutmen politik yang demokratis untuk merekrut pejabat-pejabat politik yang dipercayai masyarakat; Penerapan sistem pemilu proporsional daftar terbuka terbatas.Kata Kunci: Partai Politik; Rekrutmen Politik; Reformasi Partai Politik.